Pattern Of Chemotherapeutic Practice And Their Adverse Effects In Breast Carcinoma Patients Attending Two Public Tertiary Care Hospitals In Dhaka City - S, Afrin; SE, Noor; Alima, F; Sultana, N; Karim, R (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Cancer is a group of diseases with creation of abnormal cells which can invade adjoining parts of the body and spread to other organs. Breast cancer topped the list of the women affected with various types of cancers in Bangladesh. It alone accounts for 25% of all cancer cases and 15% of all cancer deaths among females. The present study was done to evaluate the pattern of drug management, their adverse effects and socio demographic characteristics of the patients of breast carcinoma admitted and getting chemotherapy in two tertiary hospitals of Bangladesh. Materials and Methods: It was a cross sectional observational study carried out from January to December 2015 at DMCH & NICRH. During this period, 102 patients were studied in purposive sampling technique by using a set of pre-tested structured questionnaire. Data analysis was done using SPSS version 21. Result: Most of the patients were in 4th decade (34.9%), came from low (59.6%) or middle (39.4 %) income family, were married (89.9 %), had one child (40.19 %). The mean duration of treatment for cancer was found 9.35±5.17 months. Cyclophosphamide (57.8%) and Doxorubicin (55.9%) were the most frequently prescribed drugs. Other drugs frequently used were Paclitaxel, 5 fluorouracil, Cisplatin and Gemcitabine. Nausea, vomiting, loss of hair, loss of appetite, mucositis, diarrhea and constipation were caused by any chemotherapeutic agents used whereas myelosuppression, cough, dyspnoea, hypersensitivity, amenorrhea, anemia, hyper-pigmentation, dizziness, neuropathy, metallic taste, increased risk of infection, bone pain, and allergy were evident for specific chemotherapeutic agents. Conclusions: Cyclophosphamide and Doxorubicin were more common chemotherapeutic agents used in breast cancer in Bangladesh. Difference in ranking of severity of adverse effects weredependant on demographic pattern, drug used and doses of the drugs. J.Dhaka National Med. Coll. Hos. 2017; 23 (02): 33-37